Analysis of rock mass behavior with Empirical and Numerical method for the construction of diversion tunnel, Laos. Issue 1 (January 2022) - Mboussa, D J W; Sun, S
Abstract: Tunneling construction in the mountain area is a challenge for engineers and geotechnicians because of instability due to the presence of discontinuities. The objective of this paper is the modeling of surrounding rock masses for the stability of the diversion tunnel to predict the behavior of rock masses during the excavation process for the Nam Phoun hydropower station project in Laos. Field investigation and laboratories test was realized; Empirical methods as Rock mass designation and Geological Strength Index were performed, rock masses were classified in three categories (RM-1, RM-2, and RM-3); in situ stresses were obtained from existing equations, numerical modeling was performed by the 2D plane strain finite element code Phase2 developed by Rocscience, using Generalized Hoek-Brown criterion for each type of rock masses. The results of numerical modeling show the strength zones of stresses and deformations around the tunnel and predict the instabilities around the tunnel during excavations processes. Thus, for all rock's masses, it will be necessary to consider an analysis for the supports design before the excavation's process. The findings of this study allow a clearer understanding of the importance to assess a predictive analysis of slope stability during the feasibility phase of a project by engineers to have an idea of instabilities and its significant in preventing the impact on the cost of the project.